Dynamin Binding Protein Is Required for Xenopus laevis Kidney Development - DeLay, Bridget D.; Baldwin, Tanya A.; Miller, Rachel K. (Frontiers in Physiology, 2019)
The adult human kidney contains over one million nephrons, with each nephron consisting of a tube containing segments that have specialized functions in nutrient and water absorption and waste excretion. The embryonic kidney of Xenopus laevis consists of a single functional nephron composed of regions that are analogous to those found in the human nephron, making it a simple model for the study of nephrogenesis. The exocyst complex, which traffics proteins to the cell membrane in vesicles via CDC42, is essential for normal kidney development. Here, we show that the CDC42-GEF, dynamin binding protein (Dnmbp/Tuba), is essential for nephrogenesis in Xenopus. dnmbp is expressed in Xenopus embryo kidneys during development, and knockdown of Dnmbp using two separate morpholino antisense oligonucleotides results in reduced expression of late pronephric markers, whereas the expression of early markers of nephrogenesis remains unchanged. A greater reduction in expression of markers of differentiated distal and connecting tubules was seen in comparison to proximal tubule markers, indicating that Dnmbp reduction may have a greater impact on distal and connecting tubule differentiation. Additionally, Dnmbp reduction results in glomus and ciliary defects. dnmbp knockout using CRISPR results in a similar reduction of late markers of pronephric tubulogenesis and also results in edema formation in later stage embryos. Overexpression of dnmbp in the kidney also resulted in disrupted pronephric tubules, suggesting that dnmbp levels in the developing kidney are tightly regulated, with either increased or decreased levels leading to developmental defects. Together, these data suggest that Dnmbp is required for nephrogenesis.